The Role of the Family and Social Networks as Agents of Social Control in Correctional Institution Class I (A case Study in Sukamiskin, Bandung) - Hilda Mianita (Ilomata International Journal of Social Science, 2023)
Family and social networks have a role in providing support to those in need. With the support from family and social networks, motivation in the training phase in Correctional Institution should be encouraged. However, people do not realize the importance of providing support for inventions, even though this can prevent a number of violations of use while undergoing training in Correctional Institution, such as escaping or other violations. In addition, Class I Correctional Institution at Sukamiskin is an Institution for corruptors in Indonesia, where stress level tends to be high. The former luxurious lives they used to have and enjoy are now the lives full of tension, worries and restlessness. The purpose of this research is to analyze the roles of family and social networks as social control to help them create a better situations. The method used in this study is the mixed method, a combination of both qualitative and quantitative. In this study, the sample was taken randomly, comprising 30 inmates in Class I Correctional Institution in Sukamiskin. The theory used is Hirchie's theory of social control and the stress-coping mechanism. The results of this study indicate that 66.6% of inmates believe that the presence of family and social networks are crucial. With reference to Hirchie's theory of social control, it is concluded that discouraging situations in which convicts may commit irregularities or crimes in Correctional Institution can be prevented.